Analysis of healthcare-associated infection in patients with pulmonary arterial hypertension associated with congenital heart disease in PICU: Evidence from a tertiary hospital in western China - Li, Jing-wen; Guo, Ling-wen; Tao, Si-yuan; Deng, Yu-hua; Yang, Cui; Qiao, Fu (Frontiers in Pediatrics, 2022)
Objective The present study intends to analyze the targeted surveillance and risk factors for healthcare-associated infection (HAI) in patients with pulmonary arterial hypertension associated with congenital heart disease (CHD-PAH) in a Pediatric intensive care unit (PICU), and provide basis for formulating relevant prevention and control measures of HAI. Methods Children (≤14 years old) who were admitted to the PICU for ≥2 calendar days from January 2018 to December 2021 were included. Targeted surveillance of HAI was described. Results A total of 7828 patients in PICU were monitored, and the total hospitalization days of the patients were 36174. 108 cases of HAI occurred, with a per-case infection rate of 1.38% and a per-thousand day infection rate of 2.99. 1129 patients with CHD-PAH were included, among which the total hospitalization days were 1483. In this subpopulation, 38 cases of HAI were diagnosed, with a per-case infection rate of 3.37% and a per-thousand day infection rate of 25.62. The main site of HAI was lower respiratory tract (43.51%), followed by blood infection (34.26%) and surgical site infection (9.26%). 36 strains of pathogenic bacteria were detected from patients with HAI. The top three pathogens with the highest detection rate were Klebsiella pneumoniae (6 episodes, 16.67%), Enterococcus faecium (6 episodes, 16.67%) and Acinetobacter baumannii (4 episodes, 11.11%). The incidence of VAP, CAUTI and CLABSI was 2.78, 0.08 and 1.66 per 1000 catheter days respectively. Analysis revealed that patients with CHD-PAH were younger and prone to receive surgical corrections. CHD-PAH could significantly increase the length of ICU stay, ventilator days, times of central venous catheterization and central venous catheterization days. The choice of different central venous catheter types differed significantly between the two groups. Conclusion Patients with CHD-PAH are characterized with excessive central venous catheterization operations, prolonged indwelling time, and more types of catheterization, which are considered to be risk factors for HAI, thus increasing the length of hospital stay. The clinical etiology is mainly G-bacteria, which requires reasonable selection of antibiotics and strict aseptic operation. Limiting unnecessary invasive procedures is helpful for reducing the incidence of postoperative HAI in PICU.